Investor Protections and Economic Growth - Haidar, Jamal Ibrahim (2012)
Using objective measures of investor protections in 170 countries, I establish that the level of investor protection matters for cross-country differences in GDP growth: countries with stronger protections tend to grow faster than those with poor investor protections.